(untitled) (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
Self-medication is done for the self-care. It is common practice in our surroundings as many people has been involving for the self-medication practice for the emergency condition and feeling less severity of disease according to their past experience is been the main focusing reasons for this practice in their own. This study focuses on two-way perspectives of self-medication i.e., allopathic and traditional healing. Similarly, this study highlights the age, sex, education and occupation and its association with self-medication. The aim of this study was to know the self-medication practice and its demographic factors among the residential of Helembhu Gaupalika. A cross sectional study was conducted among residents after obtaining prior consent from those willing to participate. Three hundred and seventy-one individuals participated in the study. Among 371 participants 334 (90%) practice self-medication during illness. The result shows that self-medication is mostly used in 51-60 age group (30.7%), sex (male 52.6% and female 47.4%), education (literate to higher secondary 86.3%), occupation (56.1%) and traditional healing practices (38.4%). The study reveals self-medication is commonly used by the resident of Helembhu Gaupalika. The self-medication is being one of the major problems in developing country.